1982
DOI: 10.1152/jappl.1982.53.1.272
|View full text |Cite
|
Sign up to set email alerts
|

Origin, distribution, and blood flow of bronchial circulation in anesthetized sheep

Abstract: This anatomical-physiological study was undertaken to determine the suitability of the sheep for studies of the bronchial circulation. We designated the terminal portion of the bronchoesophageal artery, which runs to the trachea at the carina, as the "carinal" artery. Postmortem injections of india ink (9 sheep) and Batson's solution (4 sheep) into the carinal artery showed that the carinal artery supplied the bronchi of all lobes except the right apical lobe; the mass of the lung containing bronchi perfused r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
3
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 0 publications
0
33
3
2
Order By: Relevance
“…Within 20 min of smoke inhalation, the bronchial blood flow increases 10-to 15-fold. Magno and Fishman (10) showed that the tracheal bronchial artery is one of the major sources of blood to the lung. We have also reported that occlusion of the bronchial artery prevented the increase in pulmonary transvascular fluid flux seen with inhalation injury (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…Within 20 min of smoke inhalation, the bronchial blood flow increases 10-to 15-fold. Magno and Fishman (10) showed that the tracheal bronchial artery is one of the major sources of blood to the lung. We have also reported that occlusion of the bronchial artery prevented the increase in pulmonary transvascular fluid flux seen with inhalation injury (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…These primary airway then branch into a series of intra-pulmonary bronchial and bronchiolar airway. Both the diameter and the length of each airway branch decrease progressively from the trachea to the periphery, where the terminal bronchioles are the most distal conducting airway (Magno and Fishman, 1982). In rodents, these bronchioles lead directly to alveolar ducts, whereas in humans and monkeys, a region of transitional respiratory bronchioles with characteristics of both bronchioles and alveoli exists between the bronchioles and the alveoli of the gas exchange area (Tyler, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypoxemia has been reported to increase (18)(19)(20) or decrease (21,22) total bronchial flow, and systemic hypercarbia has been reported to increase (12,19,22), not change (5), or decrease (21) bronchial flow.…”
Section: Introductionmentioning
confidence: 99%